Is it possible to actively and purposely make use of plasticity and adaptability in the neurorehabilitation treatment of multiple sclerosis patients? A pilot project - Rasova, K; Krasensky, J; Havrdova, E; Obenberger, J; Seidel, Z; Dolezal, O; Rexova, P; Zalisova, M (Clinical rehabilitation, 2005)
OBJECTIVE: To investigate whether neurorehabilitation is able to influence clinical parameters and brain function measured radiologically. DESIGN: A group of healthy probands was compared with two groups of multiple sclerosis (MS) patients, one of which received rehabilitative therapy. SETTING: Outpatient in a university hospital. SUBJECTS: Twenty-eight patients with multiple sclerosis (MS), 17 of whom received rehabilitative therapy, and 13 healthy controls. INTERVENTIONS: Two months of rehabilitative eclectic therapy based on principles of sensorimotor learning and adaptation. MAIN MEASURES: Multiple Sclerosis Functional Composite, Modified Fatigue Impact Scale, Beck Depression Inventory Score, Barthel Index, Environment Status Scale and Multiple Sclerosis Quality of Life--54, and functional magnetic resonance imaging (fMRI). RESULTS: Patients who underwent neurorehabilitation showed a greater drop in fatigue, depression, impairment, disability and handicap and more improvement in quality of life than those who did not receive therapy. Correlation of brain activity between the right and the left hemisphere is greater in healthy individuals than in MS patients. Neurorehabilitation resulted in a trend for increased correlation between the left and the right hemisphere in patients (approaching the standard). In comparison with control groups, signal amplitudes in anatomical areas did not show any significant changes. CONCLUSION: Clinical changes seen with neurorehabilitation were not associated with any detectable changes in fMRI observations.
Keywords: Pilot Projects; neuroplasticita; kvalita života; Physical Therapy Modalities; Humans; Case-Control Studies; Treatment Outcome; techniky fyzikální terapie; Neuronal Plasticity; studie případů a kontrol; lidé; pilotní projekty; Multiple Sclerosis; magnetická rezonanční tomografie; Quality of Life; Magnetic Resonance Imaging; roztroušená skleróza; výsledek terapie